Physical Characteristics of Bamboo and Aren’s Midrib Crafts Waste as Hydroponic Growth Media - Amaliah, Wenny; Dewi, Endang Purnama; Saputra, Oki (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The critical aspect of planting media is providing oxygen to the root; hence, the growing media should have sufficient porosity for air circulation for the plants, especially the root, and be able to store water and air. Krei craft waste from bamboo and aren’s midrib can be used as hydroponic growing media. This study aims to determine the physical characteristics of craft waste from bamboo and aren’s midrib as hydroponic growing media. The characteristics of hydroponic growing media from bamboo and aren’s midrib waste include water content, bulk density, porosity, and water holding capacity (WHC). The results of this study indicated that the values of water content, bulk density, porosity, and water holding capacity (WHC) of bamboo were 9.94%, 0.215 g/cm3, 81.6%, and 172%, and aren’s midrib were 10.07%, 0.241 g/cm3, 77.0%, and 241%, respectively. According to these results, it can be concluded that craft waste from bamboo and aren’s midrib is suitable as a hydroponic planting media.